Prediction Failure of a Wolf Landscape Model - Mech, L. David (DigitalCommons@University of Nebraska - Lincoln, 2006)
I compared 101 wolf (Canis lupus) pack territories formed in Wisconsin during 1993–2004 to the logistic regression predictive model of Mladenoff et al. (1995, 1997, 1999). Of these, 60% were located in putative habitat suitabilities 50% remained unoccupied by known packs after 24 years of recolonization. This model was a poor predictor of wolf re-colonizing locations in Wisconsin, apparently because it failed to consider the adaptability of wolves. Such models should be used cautiously in wolf-management or restoration plans.